Determinação da influência da reatividade dos grupos sangüíneos ABO e RH na etnia simplificada através da utilização de redes neurais artificiais - Aguiar, Elzenclever Freitas de (2008)
The Epidemiology is the branch of Medicine related to the study of the incidence and prevalence of the illnesses in a given population. There is growing interest in studying the ethnic susceptibility in varied illnesses, such as the falciforme anemy, that is more common in blacks and the multiple sclerosis, in Caucasians. In heterogeneous populations, where the Inter-racial marriage is frequent, the determination of the ethnicity is particularly difficult. How to define the ethnicity in a population highly mixed, as of Brazil, and to quantify the incidence of illnesses and the pertaining to school access and to the services of health for each ethnic group? Aiming at contributing to the determination of the simplified ethnicity through the individual reactivity to the reagents used in the gauging of blood group ABO and RH, this work considers a conexionist model, through MLP nets. For this, are used concepts of neural network committees with results being acquired by the method of average and specialization of the training set through conduct pattern replication (RDP). For the presented results, it was verified that, with the database used in research, it did not get resulted significant that warrants the use of this technique, for the determination, through the set of presented reagents, of the simplified ethnicity of the individuals. A great variation of classification projects, and configurations and architectures of net, had been tested. However, a significant result was presented regarding to the determination of the respective sanguine types, using itself the same joint of reagents.